Neotectonic structure of the Lakonikos gulf - PAPANIKOLAOU, D.; METAXAS, C.; CHRONIS, G. (Bulletin of the Geological Society of Greece, 2001)
Detailed single-channel seismic reflection survey has been carried out in the Lakonikos Gulf, Southern Péloponnèse, aiming to a better understanding of the neotectonic structure of the Lakonikos Basin. Our survey showed that, contrary to the model of a simple N-S asymmetric graben previously considered, a tectonic horst occurs within the tectonic graben of Lakonikos. A subsidence of more than 1000m is produced by the N-S marginal faults, whereas, the N-S faults creating the central horst structure within the Lakonikos graben are high-angle reverse faults, which have uplifted the sea bottom together with the Pleistocene and Holocene sediments by about 100m. Several E-W vertical transcurrent faults, with strike-slip motion deform the N-S structures. The central tectonic horst structure is very recent as the observed deformation of the Upper Pleistocene and Holocene sediments indicated and a transtensional geodynamic regime is suggested.